Physical activity and motor fitness for sedentary lifestyle of Iraqi students - Aziz Dawood Al -Sudani, Ali; Jabar Matar AL-Bkhati, Maytham (International Journal of Psychosocial Rehabilitation, 2020)
Background The aim of the research was comparison of motor fitness and physical activity of Iraqi students of the first and fourth years of study with mostly sedentary style of life. Material/Methods The research involved 88 students of the first year of study and 88 students of the fourth year of study of the University of Misan, Al Amarah, Misan, Iraq. Basic motor fitness test based on the International Physical Fitness Test Eurofit was used. In addition Physical Activity Questionnaire with 19 questions was filled out by the subjects. Results Almost all students assessed faculty conditions concerning equipment and facilities to practice physical activity as low or very low. Active students undertake sport trainings mostly out of their faculties. The motivation to undertake physical activity were: they like it, want to have a good health and to be slim, want to meet friends. They practice especially football, fitness exercises, walking, running, bicycle riding. Parents and teachers mostly do not encourage them to undertake physical activity. Students do not use alcohol, drugs. One sixth of them smoke cigarettes. The first and fourth year students did not differ in most of motor fitness tests, except handgrip. Older students were stronger. Conclusions The city and university administrations should establish places for all people in order to make environment prepared for exercising. It is necessary to undertake strong information action on positive influence of undertaking physical activity in order to become students and other young and older people more healthy and fit.